Emerging Tools for Emerging Symbioses - Using Genomics Applications to Studying Endophytes - Mysore V. Tejesvi (Frontiers Research Topics, 2017)
Plants are typically colonized by numerous endophyte species symbiotically without any noticeable disease symptoms. These microbes are abundant, diverse and play critical ecological roles across natural and agricultural ecosystems. Endophytes have attracted the attention of researchers due to their various beneficial effects on plants, especially in agricultural crop species. Genomic tools will enhance our understanding on the growth and nutrition requirements of this host-symbiont relationship. Recent advances in DNA sequencing technologies and bioinformatic pipelines have allowed analyzing the plant microbiome and host-endophyte interaction more effectively with limited bias. Furthermore, various studies have employed and utilized transcriptomic and genomic tools to understand the role of endophytes and their interaction with plant hosts. This electronic book covers various research articles highlighting the important developments on endophytes using transcriptomics, next generation sequencing and genomic tools.